Sustainability and efficiency: the impact of social entrepreneurship on the socio-economic development of Ukraine in the conditions of a full-scale war - Dedilova, Tetiana; Yurchenko, O.; Kononenko, Y.; Osypova, Svitlana (My University, 2024)
The article is devoted to the research of social entrepreneurship in the context of sustainability and efficiency of Ukrainian business in the conditions of a full-scale war with russia. The place of social entrepreneurship in the unity of elements of sustainable development is separately determined and directions for the creation and imple-mentation of entrepreneurial projects and sustainable development initiatives in Ukraine for the period up to 2030 are proposed. It characterizes the impact of social entrepreneurship on the socio-economic development of Ukraine as a key tool for reducing social problems and transforming the country on the basis of sustainability.
Keywords: social entrepreneurship; sustainability; development; business model; concept